84 The impact of a regulatory nudge on the overuse of low dose codeine in manitoba, canada. (20th August 2018) - Bugden, Shawn; Friesen, Kevin; Falk, Jamie
Abstract : Objectives: Low-dose codeine products (≤8 mg codeine/tablet) have been available over-the-counter from Canadian pharmacies for many years. In the era of the North American opioid crisis there has been concern about the volume of low-dose sales and their potential to contribute to the problem. This concern extended to the potential for acetaminophen/paracetamol toxicity. There has been widespread criticism about the lack of assessment by pharmacists in the provision of these products. In 2016, Manitoba became one of the few provinces to impose further regulation on the provision of low-dose codeine products. After February 2016 these products could only be dispensed with a prescription. Pharmacists were able to provide these prescriptions but only after a complete and documented assessment (sign and symptoms, medical history, length and severity of condition). In this study we explore the impact and potential unintended consequences of this regulatory nudge on low-dose codeine use. Method: A drug utilization analysis was conducted for the year before and after the policy change. Sales information was reported by the College of Pharmacists of Manitoba from the Quintiles IMS Canadian Drug Store and Hospital Purchases Audit. Prescription codeine use was assessed using the Manitoba Population Research Data Repository using data released in January 2018. The effects of this policy change on the use of other prescribed opioids were assessed by piecewise Poisson regression analysis. Results: In the year before the regulatory nudge sales data reported 52.5 million low-dose codeine tablets sold in Manitoba. This fell by 94% to 3.3 million tablets in the year after the change and this was confirmed in the research database which also showed dispensations for 3.3 million tablets. The prescribing of low-dose codeine was split evenly between pharmacists (49%) and physicians (48%). In its first year as a prescribed product, low-dose codeine use declined from 0.30 to 0.26 million tablets/month. Poisson regression analysis found no significant effect of this changeover on the trends in the utilization of higher strength codeine products, tramadol, and oxycodone with acetaminophen products. Conclusions: Manitoba's regulatory nudge reduced low-dose codeine usage by 94% without obvious negative implications. Other provincial or national policy changes should be considered to implement this simple change on a nationwide basis.